A tool for ROV-based seabed friction measurement. (March 2015) - Stanier, S.A.; White, D.J.; Chatterjee, S.; Brunning, P.; Randolph, M.F.
Highlights: A device has been developed for measuring seabed friction. It is intended to be deployed offshore using a remotely operated vehicle. The device can use plate, pipe or chain shaped tools. Analysis methods are proposed to compare measurements from each tool. Trials show the measurements are consistent and back-analysis is robust. Abstract: This paper describes a new device for measuring seabed sliding resistance in situ, and provides an associated interpretation procedure. The device is designed to use a work class ROV as a testing platform to allow measurements to be obtained without use of a specialized geotechnical survey platform. The measurements are to assist pipeline design or analysis of the sliding resistance of other on-bottom infrastructure such as anchor chains. The device has been trialled using three tools: a flat plate, a cylindrical pipe section and a length of chain. The tools are dragged axially along the seabed using the ROV thrusters or a separate hydraulic actuator. An interpretation technique has been developed to estimate the passive resistance mobilized by the faces of the tools to eliminate end effects and to account for shape effects such as wedging. Onshore-trial tests were performed in a bed of dry sand. The individual tools exhibited different overall coefficients of friction, but the back-analysis method yielded equal interface friction angles acting on all three devices, indicating internal consistency. The interface friction angle also matched shear box test results. These outcomes confirm the correct operation of the device in drained seabed conditions, and yield useful information on the sliding resistance of pipes and chains. In addition, the back-analysis method allows measurements from one shape of tool to be used to estimate the response of other objects.